The Effect of Self-Regulation on Academic Stress Among Tahfidz Students at MA Ulumul Qur'an Pagar Air - Zainab, Syarifah; Yoza, Khairan Nabila (ALACRITY : Journal of Education, 2024)
Self-regulation is an individual's ability to manage thoughts, feelings, emotions, and behaviors to meet the standards and goals they aim for as evidence of self-improvement. This ability is particularly essential for Qur'an memorization students (santri tahfidz), who not only study general subjects but also have to memorize the Qur'an. The objective of this study is to examine the influence of self-regulation on academic stress among Qur'an memorization students at Madrasah Aliyah Ulumul Qur’an Pagar Air. The research method used is quantitative. The subjects in this study consist of 146 students from Madrasah Aliyah Ulumul Qur’an Pagar Air, with the sample selected using a probability sampling technique, specifically simple random sampling. Data collection was conducted using the Likert scale method by distributing questionnaires to the research subjects. Data analysis was carried out using a simple linear regression test. The results showed that there is an influence of self-regulation on academic stress among Qur'an memorization students at Madrasah Aliyah Ulumul Qur’an Pagar Air, with an R Square value of 0.276, an F value of 55.028, and a significance value of 0.000. The influence of self-regulation on academic stress among these students is 27.6%. The aspect of self-regulation that has the highest impact on academic stress in this study is self-reflection.